Histórias contadas em Ichu-Ba: por uma proposta de valorização da oralidade no ensino de língua portuguesa - Guimarães, Elinalva Carneiro Muniz (2016)
This paper presents the results of both elaboration and execution of a didactic sequence, which aimed at amplifying the oral capacities of State School Luís Júlio Carneiro’s 7th grade students, in Ichu-BA. The Portuguese classes’ priority is, mostly, teaching grammar and writing skills believing that it is possible to promote, at school, speaking and listening moments that will lead the student to a conscious and respectable orality. Thus, we intend to offer these moments of oral practice by telling stories and using technological help. Oral stories – a common practice of knowledge and beliefs dissemination years ago – are visibly losing their space among families and communities since the advent and popularization of technological instruments such as radios, televisions and, later, cellphones and personal computers, the practice being almost restrict to people’s childhood. As they grow up, children’s contact with this spoken stories is lower, almost rare, as they have direct access to written stories. This research-intervention is based on official documents such as the PCN (1998) and the discussions on orality are based on Bakhtin (1929; 1961), Marcuschi (2010) and Ramos (2002)’s texts. Busatto (2012; 2013) Regatiere (2008), Torres & Tettamanzy (2008) uphold the pedagogical importance of telling stories in and out of school, and Libâneo (2011) Moran (1995) and others support the necessity of joining the technological resources used by students to their practice. We foresaw, in this research, some video recordings about the city’s storytellers and an internet page, both created to preserve and share the material produced during the projects development, favorably having technology as an ally to the teaching-learning process. We reached our objective in different levels, if not all, and the research proves that when the schools promote these moments of oral planning and usage constantly, storytelling becomes an efficient resource.